Kidney transplant program in Irkutsk Region - A. V. Novozhilov; S. E. Grigoriev; O. Yu. Yakovleva; S. A. Yezhikeev (Вестник трансплантологии и искусственных органов)
Introduction. Kidney transplantation (KT) is often considered the best option for renal replacement therapy (RRT), significantly improving patient outcomes. Post-transplant, life expectancy doubles, and mortality decreases more than 4-fold compared to other RRT modalities. This article presents KT outcomes in Irkutsk Region from 2018 to 2023. All procedures were performed at a single center – the Irkutsk Regional Clinical Hospital.Objective: to analyze the immediate and long-term outcomes of KT in Irkutsk Region.Material and methods. A retrospective analysis was conducted on the treatment outcomes of 125 patients with kidney failure (KF). Among them, 74 were men with a median age of 42 (35–49) years, and 51 were women with a median age of 46 (37–55) years. The median transplant waitlist time was 15.5 (range: 6–32) months. The leading cause of KF was chronic glomerulonephritis, observed in 60 patients (48%). There were no HLA matches in 36 patients (28.8%), while 38 patients (30.4%) had one match. Arterial anastomosis was primarily performed end-to-end with the external iliac artery in 121 cases (96.8%), while in 3 cases (2.4%), the internal iliac artery was used due to external iliac artery spasm. Cold ischemia time was 222 minutes (range: 162–360), and warm ischemia time was 39 minutes (range: 30–46).Results. Length of hospital stay was 16 (range: 13–25) bed days. Primary renal function was achieved in 95 patients (77%), while 25 patients (20%) experienced delayed graft function. Blood tacrolimus reached target levels by postoperative days 9–12. Creatinine level at discharge was 120 μmol/L (range: 97–165). Surgical complications occurred in 24 patients (19.2%), while urinary tract infections were observed in 36 patients (28.8%), with 17 cases (13.6%) presenting clinical symptoms. Immunosuppressive therapy was initiated in 124 patients (99.2%) using a standard triple-drug regimen (calcineurin inhibitors, mycophenolates, and glucocorticoids). One patient (0.8%) succumbed to complications from COVID-19. One-year graft survival was 94.1%.Conclusion. The immediate outcomes align with national averages. There is a consistent upward trend in the number of kidney transplants performed. Further development of the regional transplant program will enhance access to this high-tech medical service, meeting the needs of the local population.